Bosutinib, dasatinib, imatinib, nilotinib, and ponatinib differentially affect the vascular molecular pathways and functionality of human endothelial cells. Issue 1 (2nd January 2019) - Gover-Proaktor, Ayala; Granot, Galit; Pasmanik-Chor, Metsada; Pasvolsky, Oren; Shapira, Saar; Raz, Oshrat; Raanani, Pia; Leader, Avi
Abstract: The tyrosine kinase inhibitors (TKIs), nilotinib, ponatinib, and dasatinib (but not bosutinib or imatinib), are associated with vascular adverse events (VAEs) in chronic myeloid leukemia (CML). Though the mechanism is inadequately understood, an effect on vascular cells has been suggested. We investigated the effect of imatinib, nilotinib, dasatinib, bosutinib, and ponatinib on tube formation, cell viability, and gene expression of human vascular endothelial cells (HUVECs). We found a distinct genetic profile in HUVECs treated with dasatinib, ponatinib, and nilotinib compared to bosutinib and imatinib, who resembled untreated samples. However, unique gene expression and molecular pathway alterations were detected between dasatinib, ponatinib, and nilotinib. Angiogenesis/blood vessel-related pathways and HUVEC function (tube formation/viability) were adversely affected by dasatinib, ponatinib, and nilotinib but not by imatinib or bosutinib. These results correspond to the differences in VAE profiles of these TKIs, support a direct effect on vascular cells, and provide direction for future research.